2023
DOI: 10.3390/app13074303
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clear Aligner Treatment in First-Treatment and Re-Treatment Patients: A Retrospective Cohort Study

Abstract: This retrospective real-world study aimed to evaluate the outcomes of clear aligner treatment (CAT) and patient demographics of patients seeking orthodontic re-treatment who had previously received orthodontic treatment in childhood or adolescence. The study was conducted using anonymized data from DrSmile (Berlin, Germany), a CAT provider in Europe. Data were collected from a total of 2080 patients in Germany (71.5% female, 28.5% male, ranging from 18–70 years, median 29.0 years), who completed their CAT betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This suggests that a treatment plan incorporating both approaches can optimize their respective advantages in managing certain malocclusions [ 6 , 9 , 15 ]. Orthodontists’ reports of the need to refine and complete CAT cases with fixed appliances may suggest a limitation in the DTP software to estimate individual tooth movements and treatment outcomes precisely [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a treatment plan incorporating both approaches can optimize their respective advantages in managing certain malocclusions [ 6 , 9 , 15 ]. Orthodontists’ reports of the need to refine and complete CAT cases with fixed appliances may suggest a limitation in the DTP software to estimate individual tooth movements and treatment outcomes precisely [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they underwent initial and continuous training through the Clear Aligner Academy program. This program ensures that all practitioners are equipped to handle a range of cases, from simple to moderately complex clear aligner therapy (CAT), and to conduct standardized clinical examinations for appropriate case selection within the treatment scope [20]. The treatment protocol employed a series of custom-designed aligners tailored to the complexity of each case.…”
Section: Setting Participants and Sample Sizementioning
confidence: 99%
“…Previous studies on thermoformed aligners have extensively explored their resistance to staining, attributing their color stability to material properties and manufacturing processes [ 16 , 17 ]. Research has shown that thermoformed aligners retain their color when exposed to common dietary agents such as coffee, tea, and wine, primarily due to the surface characteristics and the chemical composition of the polyurethane material used [ 18 ].…”
Section: Introductionmentioning
confidence: 99%